(untitled) (Revista de Investigaciones Universidad del Quindío, 2014)
The LVDT is the main element in profile measurements using a contact profiler. Its function is to convert the stylus displacement on a voltage response changing the position of the coil core. Due to the high sensitivity of this device, 7,19mC/V/mil, it is a challenge to measure its response. The sensitivity was calculated using the primary and secondary voltage and the core displacement at full scale. This value was obtained determining the two ends of the core’s path in which the measured voltages are equal and between them the response is linear. For the LVDT conditioning we used an AD698 circuit which generates a harmonic signal with adjustable amplitude and frequency to the primary coil, and a synchronous demodulator which changes the signal of the secondary coil to a DC signal. This response increases linearly with the core position. According to the resolution, input signal, sampling time, dynamic and static benefits, communication interface and, size and price, the conversion A/D system was designed and implemented. The profile data were transmitted using USB protocol by an ATxmega microcontroller. To evaluate the performance of the conditioning system we used control patterns of 50, 5 and 1 KÅ obtaining good results.